2017
DOI: 10.1590/1980-5373-mr-2016-0692
|View full text |Cite
|
Sign up to set email alerts
|

Physical Vapor Deposited Films of a Perylene Derivative: Supramolecular Arrangement and Thermal Stability

Abstract: The analysis of supramolecular arrangement is essential to understand the role of this key factor on the optical and electrical properties of organic thin films. In this work, thin solid films of bis(phenethylimido) perylene (PhPTCD) fabricated using physical vapor deposition (PVD) technique (thermal evaporation), deposited simultaneously onto different substrates (Ag mirror, Ge, and quartz plates) contingent on the characterization technique. The main objective is to study the PhPTCD supramolecular arrangemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…The relatively good agreement between experimental and simulated Raman spectra of the rigid tetramer indicate that either or both of the PDI–spiro–PDI wings are planarized, although the extent is not certain because of the idealized model tetramers used in these calculations. Cursory comparison to Raman spectra of single PDI systems reveals similarities with the rigid Raman pattern, , but this is complicated by resonance enhancement effects in the former. Nonetheless, we expect that actual rigid tetramer geometries may experience minor alterations due to the presence of branched alkyl groups on the imide positions of each PDI unit.…”
Section: Results and Discussionmentioning
confidence: 96%
“…The relatively good agreement between experimental and simulated Raman spectra of the rigid tetramer indicate that either or both of the PDI–spiro–PDI wings are planarized, although the extent is not certain because of the idealized model tetramers used in these calculations. Cursory comparison to Raman spectra of single PDI systems reveals similarities with the rigid Raman pattern, , but this is complicated by resonance enhancement effects in the former. Nonetheless, we expect that actual rigid tetramer geometries may experience minor alterations due to the presence of branched alkyl groups on the imide positions of each PDI unit.…”
Section: Results and Discussionmentioning
confidence: 96%
“…Therefore, it was verified that the roughness of the PhPTCD LS film is greater than that of the BuPTCD, suggesting that the molecular structure may have been responsible for the differences observed between the morphologies. In addition, it is important to emphasize that the roughness values of both films obtained in this work are significantly higher than those found for PVD films of the same perylene derivatives. ,, …”
Section: Resultsmentioning
confidence: 55%
“…When these results are compared with those found for the BuPTCD and PhPTCD molecules in the form of films deposited via PVD, it is observed that the LS and PVD films of BuPTCD have the same head-on molecular organization . However, while the LS film has a head-on molecular organization, the PhPTCD PVD film has a face-on molecular organization …”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations